Characterization of NI/Zeolite Catalyst Including Specific Surface Area, Acidity, Si/Al Ratio, Cation Content in Zeolite - Donatus Setyawan Purwo Handoko; Triyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Specific Surface Area, acidity, Si/Al ratio, and cation concentration in zeolite catalysts have all been studied in relation to Ni/zeolite catalysts. The zeolite was submerged in water for 24 hours, dried, and then calcined for 3 hours at 400 oC before being incubated for 2 hours to create the Ni/zeolite catalyst. then 24 hours of stirring soaking in 6 M HCl, followed by 3 hours of refluxing with 1 M NH4Cl and 2 hours of oxygen gas oxidation. The zeolite will subsequently be impregnated with Ni, oxidized for three hours, and reduced with hydrogen gas for two hours. Additionally, a Ni/zeolite catalyst was acquired. The catalyst's metal concentration was then determined by characterizing the Ni/zeolite mixture, Si/Al ratio, specific surface area, and acidity of the catalyst. The outcomes of the characterisation are as follows: Ca and Fe are the main metals present in the Ni/zeolite catalyst, with only trace amounts of Na, Mg, and other metals (5 mg/gram of catalyst) present. In the meantime, the catalyst's acidity was 0.24 mmol/gram catalyst acidity, its surface area was 2.18 m2/gram catalyst surface area, and its Si/Al catalyst ratio was 10.21